Way of compost application for organic farming - Khan, MAI; Hira, MHR; Rahaman, S; Moni, ZR; Hussen, MAM; Someya, T; Ueno, K (SAARC Journal of Agriculture, 2019)
Application of composts is an alternative of synthetic agrochemicals for eco-friendly farming. Work is limited on the effective and economic way of compost application in Bangladesh. A study was done at the Field Science Center, Saga University, Japan with green tea waste – rice bran compost (GRC) application. Radish (Raphanus sativus L.), spinach (Spinacia oleracea L.) and komatsuna (Brassica rapa var. pervidis) were used as test plants. GRC was applied at 1.0 kg m-2 by mulching on soil after seeding. It enhanced seed germination, seedling growth and improved crop yield of spinach and radish grown in a controlled condition. Among the two application methods, post-sowing mulching (PSM) reduced water loss from upper soil surface, thus enhanced seed germination and better growth compared to pre-sowing incorporation (PSI) system. This study also suggests that improper compost incorporation to soil may impair seed germination, seedling growth and likely crop yield. SAARC J. Agri., 17(1): 211-217 (2019)